P53 induces miR‐199a‐3p to suppress mechanistic target of rapamycin activation in cisplatin‐induced acute kidney injury. Issue 10 (30th May 2019) - Yang, Aicheng; Liu, Fanna; Guan, Baozhang; Luo, Zhi; Lin, Jiehua; Fang, Wan; Liu, Longhui; Zuo, Wanli
Abstract: How p53 participates in acute kidney injury (AKI) progress and what are the underlying mechanisms remain illusive. For this issue, it is important to probe into the role of p53 in cisplatin‐induced AKI. We find that p53 was upregulated in cisplatin‐induced AKI, yet, pifithrin‐α inhibites the p53 expression to attenuated renal injury and cell apoptosis both in vivo cisplatin‐induced AKI mice and in vitro HK‐2 human renal tubular epithelial cells. To knock down p53 by siRNA significantly decreased the miRNA, miR‐199a‐3p, expression in HK‐2 cells. Blockade of miR‐199a‐3p significantly reduced cisplatin‐induced cell apoptosis and inhibited caspase‐3 activity. Mechanistically, we identified that miR‐199a‐3p directly bound to mechanistic target of rapamycin (mTOR) 3′‐untranslated region and overexpressed miR‐199a‐3p reduce the expression and phosphorylation of mTOR. Furthermore, we demonstrated that p53 inhibited mTOR activation through activating miR‐199a‐3p. In conclusion, our findings reveal that p53, upregulating the expression of miR‐199a‐3p affects the progress of cisplatin‐induced AKI, which might provide a promising therapeutic target of AKI. Abstract : We identified that mechanistic target of rapamycin (mTOR) was a target gene of miR‐199a‐3p, and that miR‐199a‐3p mimics could inhibit expression of mTOR, which consequently reduced its phosphorylation. P53 inhibited mTOR activation through activating miR‐199a‐3p.